Sidney Weintraub and American Post Keynesianism: 1938-1970 - E. Roy Weintraub (Duke University, Center for the History of Political Economy (CHOPE), 2014)
Sidney Weintraub (1914–1983) was an American economist who spent most of his career at the University of Pennsylvania. A distinguished economic theorist (and the author's father), he was a co - founder of the Journal of Post Keynesian Economics , and the leading figure in the US in the early years of the Post Keynesian movement. This article shows how the early development of American Post Keynesianism, despite claims to the contrary by historians of Post Keynesianism, had no connection to the UK group centered around Joan Robinson in Cambridge.
Keywords: B2; B3; B5; 330; Sidney Weintraub; Post Keynesian economics; Paul Davidson; wage-price inflation